2016
DOI: 10.1111/mve.12161
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of individual members of the mosquito Anopheles maculipennis complex in Germany identified by newly developed real‐time PCR assays

Abstract: Owing to their role as vectors of malaria parasites, species of the Anopheles maculipennis complex (Diptera: Culicidae) Meigen were intensively studied in the past, but with the disappearance of malaria in Germany in the middle of the last century, the interest in this field of research declined. A comprehensive ecological analysis of the current species distribution for Germany is lacking. Between 2010 and 2013, a total of 1445 mosquitoes of the An. maculipennis complex were collected at 72 different sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…messeae had a negative correlation with the maximum temperature of the warmest month and altitude, whereas the probability of occurrence of An. daciae had a positive correlation [98]. In addition, An.…”
Section: An Messeae and An Daciae Differ In Their Ecological Prefermentioning
confidence: 88%
See 1 more Smart Citation
“…messeae had a negative correlation with the maximum temperature of the warmest month and altitude, whereas the probability of occurrence of An. daciae had a positive correlation [98]. In addition, An.…”
Section: An Messeae and An Daciae Differ In Their Ecological Prefermentioning
confidence: 88%
“…messeae occupy regions with temperate oceanic and humid continental climates according to the Eurasian Koppen-Geiger climate classification system [97]. These two species often occur in sympatry [33,[35][36][37][38][39]98,99] but their ecological niches do not completely overlap. A recent study conducted in Germany demonstrated that the probability of occurrence of An.…”
Section: An Messeae and An Daciae Differ In Their Ecological Prefermentioning
confidence: 99%
“…to humans. However, future studies might use recent molecular typing techniques [5456] to identify the most likely vectors for Dirofilaria spp. in these species complexes.…”
Section: Discussionmentioning
confidence: 99%
“…messeae had a negative correlation with the maximum temperature of the warmest month and altitude, whereas the probability of occurrence of An. daciae had a positive correlation [75]. In addition, An.…”
Section: But Their Ecological Niches Do Not Completely Overlap a Recmentioning
confidence: 88%